The Implementation of Integrity Values to Foster Anti-Corruption Attitudes in Elementary School Students - Heryanto, Debi; Susanti, Atika; Darmansyah, Ady (Universitas Muhammadiyah Mataram, 2023)
Anti-corruption education plays a crucial role in addressing the issue of corruption. The rise in corruption cases showcased on various social media platforms indicates the urgency of preventing and eliminating its adverse effects on the nation's economy, core values, and state ideology. This research aims to describe the implementation of Integrity Values to Foster Anti-Corruption Attitudes in Elementary School Students. The research methodology used is a qualitative descriptive method. The subjects in the research include both teachers and students. Specifically, the study encompassed three teachers and nine students in the 4th grade. Research instruments used observation guidelines, interview guides, and documentation. Data were collected through observation, interviews, and documentation. Data analysis was conducted through several steps, including data collection, data reduction, data presentation, and drawing conclusions. To ensure the validity of the data, this research examined four dimensions: credibility, transferability, dependability, and confirmability. The results of this research indicate that the implementation of integrity values in the effort to foster anti-corruption attitudes among students at Elementary School has been carried out through various activities, including: (1) The